Myoblast seeded bovine pericardium for repair of abdominal wall defect - Abu Bakar @ Zakaria, Md Zuki; Mohamed Mustapha, Noordin; Mohammed Alitheen, Noorjahan Banu; Tsedeke, Ayele Taddese (2009)
The present invention comprises myoblast seeded bovine pericardium and a method of making the same. The preferred embodiment, biological biomaterials which can be used for reconstruction of abdominal wall defects for regeneration o skeletal muscle both in human medicine and veterinary medicine. The present invention also provides a novel method of making/ preparation which possesses an excellent biocompatibility as well as an increased stability of the grant thereby following of seeding of myoblast on the bovine pericardium.